Knowledge, Awareness, and Practice Regarding Sleep Quality and Sleep Hygiene Among UTHM Students - Izzhanani Huda Hilmi Iskandar; Iffah Irdina Saiful Hazmi; Nawi, Adnin Afifi; Siti Norziahidayu Amzee Zamri; Abdul Hamid, Muhanizah (Multidisciplinary Applied Research and Innovation, 2024)
University students are mostly at risk for developing sleep disorders. Therefore, this study is conducted to assess and compare the knowledge, awareness and practice levels of sleep quality and sleep hygiene between Year 1 and Year 2 diploma students in UTHM Pagoh. This study also consider the relation between knowledge, awareness and practice levels of sleep quality and sleep hygiene. In this study, a cross-sectional survey has been distributed to 130 diploma students by using google form questionnaire. Data collected was analysed by using Statistical Package for Social Sciences (SPSS) version 27. The result shows that both Year 1 and Year 2 of diploma students have a basic knowledge and awareness regarding to sleep quality and sleep hygiene but did not apply them in the real life as a routine. Moreover, there is a weak positive correlation between practices of sleep quality and sleep hygiene.